(untitled) (TAMADDUN NURI JURNALI, 2024)
This article describes the socio-philosophical basis of training of personnel with scientific potential in internal affairs bodies. In the conditions of the current globalization and market economy, the cultivation of high-potential, knowledgeable, responsible, competitive personnel has become an urgent issue more than ever. A completely new stage is being taken in terms of providing internal affairs bodies with professional personnel in all aspects.